Kirschner Wire Fixation Versus Mini Plate Fixation in Multiple Metacarpal Shaft Fractures of Hand to Compare Early Range of Motion in Hand - Muhammad Zubair Farooq, Muhammad Asghar Essa, Inamullah, Yousaf Gul, Shafaat Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Metacarpal bone plays vital role in supporting motor functions of the human palm and is subjected to frequent stress. If a fracture of the metacarpal bone occurs, it can destabilize the palm, disrupt muscular-tendon tension, impair functions of palm joints, and have adverse impacts on the daily life and work of the patient. Objectives: To compare early range of motion (ROM) in hand following K-wire fixation versus mini plate fixation in patients with multiple metacarpal shaft fractures. Methods: Cross-sectional analysis of patients with multiple metacarpal shaft fractures was done at Mufti Mehmood Memorial Teaching Hospital, between 2021 and 2022, and comprised 108 patients managed with K-wire Fixation and mini plate fixation. The success rate as well as clinical outcome of both techniques was measured as early ROM in the hand, which was assessed at eight weeks post-surgery using DASH scores. Results: Majority of patients (p<0.05) were males (73.14%), common fractures (p<0.05) were closed type (75.03%), right sided (62.96%) and common cause of injury (p<0.05) was traffic accidents (n=48), industrial accidents (n=13), fall (n=12), agriculture accidents (n=12) and assault (n=10). Our findings revealed that occurrence of complications was significantly higher among the patients of group K-wire fixation (11.11%) than mini wire fixation (6.48%) and assessment of ROM through DASH score system of mini plate fixation was better than K-wire fixation. Practical implication The surgeons will confidently apply mini plate fixation in patients with multiple shaft fractures rather than K-wire fixation after reading this article. Conclusion: Mini plate fixation may be more effective than K-wire fixation in restoring early ROM in the hand following surgery for multiple metacarpal shaft fractures. Keywords: DASH scoring; Palm fracture; Range of motion; Shaft fracture.